New genus and new combination of Deltocephalinae (Insecta: Hemiptera: Cicadellidae) - Camisão, Beatriz M.; Dietrich, Christopher H. (Zootaxa, 2022)
Based on study of the holotype of Scaphytopius (Tumeus) rubidus DeLong, 1980, it was determined that this species does not belong in any genus of the subfamily Deltocephalinae described so far. To accommodate this species, we describe and illustrate a new genus in the tribe Bahitini, Anavilhanas gen. nov., and propose the new combination, Anavilhanas rubida (DeLong) comb. nov.